RISK MANAGEMENT OF EXPOSURE TO BIOLOGICAL AGENTS AMONG WORKERS IN WASTEWATER TREATMENT PLANTS DURING THE COVID-19 OUTBREAK - Elka Toseva; Stanislava Harizanova (Peytchinski Publishing, 2023)
Purpose: To systematize the activities and relationships between employers, workers, and occupational health services in the process of risk management of exposure to biological agents in wastewater treatment plants (WWTPs) during the COVID-19 outbreak. Material/Methods: We studied the Bulgarian and European Union legislation and the recommendations of international organizations related to risk management of exposure to COVID-19 concerning workers in WWTPs from March 2020 to September 2021. Results: The EU and Bulgarian legislation has been updated with a focus on risk management of exposure to the SARS-CoV-2, including workers from WWTPs. Some of the Coronaviridae that are known to be pathogenic remain in the second group according to the degree of danger, while Coronaviridae such as SARS-virus, MERS-virus and SARS-CoV-2 are evaluated and classified in group 3 according to the level of risk of infection. The employers must take measures to protect workers in accordance with the new, higher level of danger. We systematized risk management measures. Conclusion: Bulgarian and international legislation on health and safety at work has been updated in the period 2020-2021 with an emphasis on the risk management of exposure to biological agents at work.Co-operation between employers and workers in WWTPs, and occupational health services is an essential part of the risk management process, including prevention of outbreaks of work-related infectious diseases such as coronavirus disease 2019 (COVID-19).